2013
DOI: 10.1371/journal.pone.0079543
|View full text |Cite|
|
Sign up to set email alerts
|

Trastuzumab Alters the Expression of Genes Essential for Cardiac Function and Induces Ultrastructural Changes of Cardiomyocytes in Mice

Abstract: Treatment with trastuzumab, a humanized monoclonal antibody directed against the extracellular domain of Human Epidermal Growth Factor Receptor 2 (HER2), very successfully improves outcomes for women with HER2-positive breast cancer. However, trastuzumab treatment was recently linked to potentially irreversible serious cardiotoxicity, the mechanisms of which are largely elusive. This study reports that trastuzumab significantly alters the expression of myocardial genes essential for DNA repair, cardiac and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 55 publications
5
100
0
3
Order By: Relevance
“…A B D C induced cardiotoxicity is HER2 dependent (25)(26)(27)(28)(29). We used both cellular and mouse model systems to investigate a clinically relevant case of drug-induced hepatotoxicity and to elucidate the possible mechanisms of T-DM1-induced hepatotoxicity.…”
Section: Control Trastuzumab T-dm1 T-dm1mentioning
confidence: 99%
See 3 more Smart Citations
“…A B D C induced cardiotoxicity is HER2 dependent (25)(26)(27)(28)(29). We used both cellular and mouse model systems to investigate a clinically relevant case of drug-induced hepatotoxicity and to elucidate the possible mechanisms of T-DM1-induced hepatotoxicity.…”
Section: Control Trastuzumab T-dm1 T-dm1mentioning
confidence: 99%
“…Murine model has been widely used to study the mechanisms of trastuzumab-induced cardiotoxicity (25)(26)(27)(28)(29). Riccio and colleagues have shown that trastuzumab binds to mouse HER2 (26) and that mice treated with trastuzumab have reduced left ventricular ejection fraction (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using C57BL/6 mouse model, we have previously reported that trastuzumab treatment induced alteration in myocardial expression of genes that are critically involved in cardiac and mitochondrial functions, adaptation to stress, and DNA repair (12). We observed that these genetic changes are associated with increased myocardial oxidative and nitrative stress, and potentially activated apoptotic pathways, leading to elevated serum troponin-1 and cardiac myosin light chain-1 (cMLC1) levels (12).…”
Section: Introductionmentioning
confidence: 99%